2022
DOI: 10.1177/00343552221087178
|View full text |Cite
|
Sign up to set email alerts
|

Vocational Rehabilitation in the COVID-19 Era: The Importance of Supervision

Abstract: The rehabilitation counseling profession, as an essential career, has been facing unforeseen and unprecedented complications as a result of the coronavirus-19 pandemic. As practitioners were required to begin completing their work virtually or using telehealth modalities, it became apparent that may be gaps in preparation for such a shift. It is as yet unknown what implication these changes have on employment rates of people with disabilities, in addition to other markers for independence (e.g., independent li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…Supervision was most often provided via the telephone and videoconferencing, and least often provided via text messaging and social networking during the pandemic. Although the present study did not measure satisfaction with supervision, other researchers have reported that rehabilitation counselors were generally satisfied with supervision during the pandemic ( Levine et al, 2022 ). Hopefully the use of technology-based supervision continues beyond the pandemic given the advantages of increased access to supervisors in different locations.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Supervision was most often provided via the telephone and videoconferencing, and least often provided via text messaging and social networking during the pandemic. Although the present study did not measure satisfaction with supervision, other researchers have reported that rehabilitation counselors were generally satisfied with supervision during the pandemic ( Levine et al, 2022 ). Hopefully the use of technology-based supervision continues beyond the pandemic given the advantages of increased access to supervisors in different locations.…”
Section: Discussionmentioning
confidence: 66%
“…The extreme contagiousness of the coronavirus (COVID-19) pandemic resulted in social distancing mandates and shelter-in-place orders starting in March 2020 ( Levine et al, 2022 ; Pebdani et al, 2022 ). With an overnight shift to remote work, rehabilitation counselors had to quickly navigate and gain the technological and professional competencies necessary to provide technology-assisted services ethically and effectively ( Hartley & Bourgeois, 2020 ).…”
mentioning
confidence: 99%
“…In general, this specific area of the literature has been largely uncharted. Several articles have addressed the need for DEI in the profession (e.g., Alston et al, 2006;Harley et al, 2008;Kelsey & Smart, 2012;Levine et al, 2022). There have also been articles explicitly addressing the decay of professional organizations (Tansey & Garske, 2007), declining professional membership (Phillips & Leahy, 2012), the dilution of our professional identity (Zanskas, 2017), and most recently, potential threats to the profession (Nerlich et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The current study was unable to determine if this was also a factor as to whether Veterans were not accepted into the program (eg, perhaps they disclosed they were not interested in pursuing employment and wanted to be in the TW program that provides tax-free payments). Additionally, the impact of COVID-19 may explain disparities in employment rates at closure during the post-implementation phase of Policy Directive 1163, as a little over 1 year the COVID-19 pandemic changed the landscape of the United States, and Vocational Rehabilitation service delivery models in the public sector [25][26][27][28][29][30] and the implementation of telemedicine (VA Video Connect) occurred during the COVID-19 pandemic. [31][32][33]…”
Section: Limitationsmentioning
confidence: 99%